Fabrication of sub-1 nm gap electrodes using metal-mask patterning and conductivity measurements of molecules in nanoscale spaces. Issue 84 (21st November 2017) - Naitoh, Yasuhisa; Albrecht, Ken; Wei, Qingshuo; Yamamoto, Kimihisa; Shima, Hisashi; Ishida, Takao
Abstract : Fabrications of sub-1 nm gap Au electrodes using a metal mask for patterning were achieved. Because the procedure does not involve wet processing, the ranges of possible electrode and substrate materials for the electrodes are greatly expanded. Abstract : We developed a procedure for fabricating sub-1 nm gap Au electrodes using a metal mask for electrode patterning. Self-aligned nanogap formation was achieved using an electromigration method during metal deposition. We also measured the electric conductivities of organic molecules using the new nanogap electrodes. Because the new procedure does not involve wet processing, the ranges of possible electrode and substrate materials for the nanogap electrodes are greatly expanded. Finally, we discussed the molecular orbital energies of bridging and nonbridging 1, 4-benzenedithiol molecules between Au electrodes. The new procedure for the fabrication of nanogap electrodes is expected to be useful for measuring the electrical properties of various nanoscale materials.